The Influence of Customer Relationship Management, Brand Ambassador and E-Commerce Innovation on Tokopedia User Loyalty in Jabodetabek (Case Study of Generation Z) - Zaib Syahrul Mubaroq; Sutopo (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
This study aims to analyze the direct effect of the variables Customer Relationship Management, Brand Ambassador and E-Commerce Innovation on Tokopedia User Loyalty in Jabodetabek with Generation Z as the research object.This research is a quantitative research with an associative approach. The type of data used is primary data obtained through questionnaires that have been distributed and secondary data that researchers obtained from literature relating to the problems studied. The data analysis technique used is descriptive statistics and structural equation modeling (SEM) analysis with the partial least squares (PLS) method, all of which will be processed in the SmartPLS 3 application. The results of this study found that there was a positive and significant influence between the three independent variables in this study, namely the variable customer relationship management, brand ambassadors and e-commerce innovation on the loyalty of generation z Tokopedia users in Jabodetabek. Keywords: Customer Relationship Management, Brand Ambassador, E-Commerce Innovation Customer Loyalty.